Balancing Time in College: Examining Time-Use and Academic Outcomes of Students in a Comprehensive College Transition Program - Elizabeth S. Park; Elise Swanson (SAGE Publishing, 2021)
Using a randomized control trial design, this study examines the extent to which a comprehensive college transition program (CCTP) shapes students' time-use during their first 3 years in college. The CCTP provides comprehensive student-centered support as well as a generous scholarship. We compare students who had access to the CCTP with those who only received the scholarship. Findings indicate that both student groups spent similar amounts of time working for pay, studying, and on social media, and time-use had no differential bearing on college GPA by treatment status. In an exploratory analysis of program components, we find correlational evidence that academic-related interactions with faculty are positively associated with hours spent studying. We consistently find that the strongest predictor of time-use in college is how students spend their time in high school, suggesting that interventions aimed at shaping students' time-use may be most effective if they are targeted at students' precollege years.